2018
DOI: 10.1111/1440-1681.12971
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analgesic efficacy of pregabalin administered according to either a prevention protocol or an intervention protocol in rats with cisplatin‐induced peripheral neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a type of peripheral neuropathic pain that may be dose-limiting in patients administered potentially curative cancer chemotherapy dosing regimens. In cancer survivors, persistent CIPN adversely affects patient quality of life and so adjuvant drugs (anticonvulsants eg pregabalin or antidepressants eg amitriptyline) are recommended for the relief of CIPN. However, most studies in rodent models of CIPN involve administration of single bolus doses of adjuvant dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(52 reference statements)
2
3
0
Order By: Relevance
“…Similarly, it was reported that the CSP-induced excessive mitochondria activation and ROS production was inhibited in the peripheral neurons by the antioxidant properties of PGAB, suggesting inhibition of excessive Ca 2+ entry through membrane channel (TRPV1) (Sasaki et al 2014;Marwaha et al 2016). Decrease of CSP-induced neuropathy and neurotoxicity in the DRG neurons of rats was recently reported (Seto et al, 2017;Han et al 2018) and the reports confirmed results of current study.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, it was reported that the CSP-induced excessive mitochondria activation and ROS production was inhibited in the peripheral neurons by the antioxidant properties of PGAB, suggesting inhibition of excessive Ca 2+ entry through membrane channel (TRPV1) (Sasaki et al 2014;Marwaha et al 2016). Decrease of CSP-induced neuropathy and neurotoxicity in the DRG neurons of rats was recently reported (Seto et al, 2017;Han et al 2018) and the reports confirmed results of current study.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present experiment confirmed that in mice, similarly to humans, oxaliplatin induced cold allodynia-a core symptom of neuropathic pain caused by this cytotoxic drug. After a single dose of oxaliplatin, cold allodynia was persistent and it was maintained for at least 7 days, which is consistent with the previous reports (Furgała, Fijałkowski, Nowaczyk, Sałat, & Sałat, 2018;Han, Kuo, Nicholson, Corradinni, & Smith, 2018;Kono et al, 2013;Nakagawa & Kaneko, 2017;Sałat, Furgała, & Sałat, 2019;Sałat et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…For example, rodent CIPN models consistently show mechanical hypersensitivity of the paw. 10,15,19 By contrast, only 5 of the 24 participants we tested (21%) reported static mechanical allodynia. This decreased mechanosensitivity is concordant with prior research in humans with CIPN.…”
Section: Discussionmentioning
confidence: 81%